Sarcopenia is associated with severe coronary atherosclerosis in male patients with coronary artery disease - Т. A. Raskina; I. I. Grigorieva; М. V. Letaeva; V. I. Ivanov; V. V. Masenko (Фундаментальная и клиническая медицина, 2020)
Aim. To investigate the association between coronary atherosclerosis and sarcopenia in male patients with coronary artery disease (CAD). Material and Methods. We enrolled 79 male patients with CAD verified by coronary angiography (median age 63 (57; 66) years). Patients were stratified according to the severity of coronary atherosclerosis: 1) 1 or 2 affected coronary arteries; 2) 3 affected coronary arteries; 3) lesions in the left main coronary artery (LMCA), with or without other coronary arteries involved. Sarcopenia was diagnosed according to the recommendations of the European Working Group on Sarcopenia in Older People (EWGSOP) which include examination examining of muscle strength, mass and function. Patients were also divided into those without sarcopenia (n = 31), those with presarcopenia (n = 21), and those with sarcopenia (n = 27). Results. Severity of coronary atherosclerosis inversely correlated with the musculoskeletal index (r = - 0.227, p = 0.047). A higher prevalence of LMCA lesions was noted in patients with sarcopenia compared with those with presarcopenia or without sarcopenia (29.6% vs. 20.0% vs. 13.3%, respectively). Severe CAD (3 affected coronary arteries or LMCA lesions was associated with a reduction in the musculoskeletal index with sensitivity of 68.1% and specificity of 56.7% (area under the curve = 0.634; 95% CI: 0.515-0.741; p = 0.028; Youden's index 0.248). Conclusion. Sarcopenia is associated with increased severity of CAD.